2020
DOI: 10.1186/s12974-020-01741-4
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination in early Alzheimer’s disease rescues amyloidosis and ameliorates cognitive deficits in APP/PS1 mice by inhibiting regulatory T cells

Abstract: Background: Alzheimer's disease (AD) is a neurodegenerative disorder strongly correlated with a dysfunctional immune system. Our previous results demonstrated that inactivated influenza vaccine (IIV) facilitates hippocampal neurogenesis and blocks lipopolysaccharide (LPS)-induced cognitive impairment. However, whether IIV improves cognitive deficits in an AD mouse model remains unclear. In addition, early interventions in AD have been encouraged in recent years. Here, we investigated whether IIV immunization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 57 publications
0
34
2
Order By: Relevance
“…In the last few years, evidence has accumulated pointing to the ability of immune stimuli to modulate neurogenesis, synaptic plasticity, in addition to cognitive and behavioral function ( Xia et al., 2014 ; Li et al., 2015 ; Li et al., 2016 ; Yang et al., 2016 ; Qi et al., 2017 ; Yang et al., 2020 ; De Sousa et al., 2021 ). These findings support the concept of consistent communication and interrelationship between the nervous and immune systems, as plastic and cognitive systems ( Jerne and Cocteau, 1984 ; Pert et al., 1985 ; Cohen, 1992 ; Sawada et al., 1993 ; Josefsson et al., 1996 ; Amenta et al., 2002 ; McKenna et al., 2002 ; Daniel-Ribeiro and Martins, 2017 ) and the use of immunomodulation as a promising approach in the treatment of neurocognitive and behavioral sequelae of infectious diseases.…”
Section: Therapeutic Approaches To Neurocognitive and Behavioral Sequ...mentioning
confidence: 99%
“…In the last few years, evidence has accumulated pointing to the ability of immune stimuli to modulate neurogenesis, synaptic plasticity, in addition to cognitive and behavioral function ( Xia et al., 2014 ; Li et al., 2015 ; Li et al., 2016 ; Yang et al., 2016 ; Qi et al., 2017 ; Yang et al., 2020 ; De Sousa et al., 2021 ). These findings support the concept of consistent communication and interrelationship between the nervous and immune systems, as plastic and cognitive systems ( Jerne and Cocteau, 1984 ; Pert et al., 1985 ; Cohen, 1992 ; Sawada et al., 1993 ; Josefsson et al., 1996 ; Amenta et al., 2002 ; McKenna et al., 2002 ; Daniel-Ribeiro and Martins, 2017 ) and the use of immunomodulation as a promising approach in the treatment of neurocognitive and behavioral sequelae of infectious diseases.…”
Section: Therapeutic Approaches To Neurocognitive and Behavioral Sequ...mentioning
confidence: 99%
“…These data indicate that AD patients can preserve their immune response to the vaccines, but the effectiveness of the vaccines may gradually decrease with age. Animal studies have shown that the systemic immunity induced by influenza vaccination can inhibit the systemic immune suppression caused by Treg cells and restore the ability of microglia to clear Aβ, thus improving cognitive dysfunction [ 55 ]. No serious adverse reactions from the inactivated influenza vaccine were observed in patients with neurodegenerative diseases compared with a control group [ 54 ].…”
Section: Neurodegenerative Diseases and Sars-cov-2 Vaccinesmentioning
confidence: 99%
“…As a next step, a shift from active to passive immunization is now under way in AD models [ 75 ]. It is regarded as more safe, to be better controlled and may also be efficacious [ 79 , 80 , 81 , 82 ]. However, will vaccination against aggregated β-amyloid plaques be beneficial for other pathological processes associated with AD, like the tau-protein pathology?…”
Section: Dementia Syndromesmentioning
confidence: 99%